2013
DOI: 10.1089/dia.2013.0013
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Continuous Subcutaneous Insulin Infusion Combined with Insulin Sensitizers Rosiglitazone, Metformin, or Antioxidant α-Lipoic Acid in Patients with Newly Diagnosed Type 2 Diabetes Mellitus

Abstract: Background: Short-term continuous subcutaneous insulin infusion (CSII) in patients with newly diagnosed type 2 diabetes has been proved effective in improving metabolic control and b-cell function, thus inducing long-term drug-free remission. A randomized controlled trial was conducted to investigate whether CSII in combination with rosiglitazone, metformin, or a-lipoic acid separately brings about extra benefits. Patients and Methods: One hundred sixty patients with newly diagnosed type 2 diabetes were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Hypoglycemia is associated with glucose fluctuations, numerous adverse events and even increased mortality. In previous reports, some hypoglycemic episodes were seen during SIIT. However, to our knowledge, a detailed description of hypoglycemic events, as well as how hypoglycemia affects clinical outcomes has not been previously described, although this is important for making clinical decisions on setting glycemic targets and titrating the insulin dose.…”
Section: Introductionmentioning
confidence: 94%
“…Hypoglycemia is associated with glucose fluctuations, numerous adverse events and even increased mortality. In previous reports, some hypoglycemic episodes were seen during SIIT. However, to our knowledge, a detailed description of hypoglycemic events, as well as how hypoglycemia affects clinical outcomes has not been previously described, although this is important for making clinical decisions on setting glycemic targets and titrating the insulin dose.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies confirmed that adjunct metformin with intensive therapies were associated with a significant reduction in daily insulin requirements and less increase in body weight. However, no proved reduction in HbA1c or hypoglycaemic episode was found . Therefore, when taking all these findings together, we could hardly conclude a protective effect of CSII therapy as compared with MDI therapy or benefits of metformin therapy when added to this insulin regimen regarding to reducing glucose variability and hypoglycaemic risk.…”
Section: Discussionmentioning
confidence: 84%
“…However, no proved reduction in HbA1c or hypoglycaemic episode was found. [15][16][17] Therefore, when taking all these findings together, we could hardly conclude a protective effect of CSII therapy as compared with MDI therapy or benefits of metformin therapy when added to this insulin regimen regarding to reducing glucose variability and hypoglycaemic risk.…”
Section: Continuous Subcutaneous Insulin Infusion With Pump Therapy Hasmentioning
confidence: 95%
“…Anecdotally, our own clinical experience with patients and their families has repeatedly shown that following STII therapy, some patients are able to sustain prolonged remissions [periods of euglycaemia] despite having discontinued drug therapy. There are also numerous formal clinical studies demonstrating that STII therapy can normalize glycaemic control, improve beta‐cell function, and/or restore first‐phase insulin secretion and decrease insulin resistance in newly diagnosed type 2 diabetes . STII therapy has also been favourably assessed in a recent meta‐analysis as well as in review articles, where it has been either the focus of the review (e.g.…”
Section: Evidence Supporting Stii Therapymentioning
confidence: 99%
“…To date, the clinical application of STII therapy in newly diagnosed patients has been very heterogeneous . As these reports indicate, STII therapy has been evaluated in single‐arm as well as comparative studies, conducted in hospital as well as outpatient settings, and delivered via continuous subcutaneous insulin infusion [CSII] or multiple daily injections [MDI].…”
Section: Introductionmentioning
confidence: 99%